2004
DOI: 10.1158/0008-5472.can-04-1568
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression by Tumor-Derived p53 Mutants

Abstract: ABSTRACTp53 mutants with a single amino acid substitution are overexpressed in a majority of human cancers containing a p53 mutation. Overexpression of the mutant protein suggests that there is a selection pressure on the cell indicative of an active functional role for mutant p53. Indeed, H1299 cells expressing mutant p53-R175H, p53-R273H or p53-D281G grow at a faster rate compared with a control cell line. Using p53-specific small interfering RNA, we show that the growth rate of mutant p53-expressing cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 46 publications
3
90
0
Order By: Relevance
“…We next examined the effect of the dominant-negative (p53V143A) and two cancer-specific mutants of p53 with distinct biological activities (p53R175H or p53R280K) on CXCR4 reporter activity (Scian et al, 2004). Neither the dominant-negative mutant nor cancer-specific mutants repressed CXCR4 reporter activity, suggesting that cancer-specific mutations abrogate the ability of p53 to repress CXCR4 expression ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the effect of the dominant-negative (p53V143A) and two cancer-specific mutants of p53 with distinct biological activities (p53R175H or p53R280K) on CXCR4 reporter activity (Scian et al, 2004). Neither the dominant-negative mutant nor cancer-specific mutants repressed CXCR4 reporter activity, suggesting that cancer-specific mutations abrogate the ability of p53 to repress CXCR4 expression ( Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Microarray analyses have shown that the overexpression of mutant p53 in different cell lines is capable to modulate the expression of many transcripts (Hoh et al, 2002;O'Farrel et al, 2004;Scian et al, 2004;Weisz et al, 2004;Tepper et al, 2005;Zalcenstein et al, 2006). Although a growing pattern of target genes has been established for wt-p53 and other transcription factors closely linked to cancer, the definition of a group of potential mutant p53 target genes needs to be solved yet.…”
Section: Pattern Of Target Genesmentioning
confidence: 99%
“…Genome-wide approaches have shown that mutant p53 is capable of modulating the expression of large patterns of transcripts (Figure 2). These findings indicate that mutant p53 might function as a transcription factor capable to turn on and off specific set of genes in response to different stimuli (Margulies and Sehgal, 1993;Subler et al, 1994;Tsutsumi-Ishii et al, 1995;Ludes-Meyers et al, 1996;Deb et al, 1998;Frazier et al, 1998;Lee et al, 2000;Iwanaga and Jeang, 2002;Scian et al, 2004Scian et al, , 2005Mizuaray et al, 2006). Consequently, mutant p53 might trigger different pathways that represent the molecular basis of the large spectrum of gain-of-function activities, which ranges from the resistance to anticancer treatments to genomic instability and increased metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Mutp53 was also shown to enhance colony formation when overexpressed in p53-null mouse fibroblasts and human lung cancer-derived cells (Murphy et al, 2000;Deb et al, 2002;Weisz et al, 2004;Scian et al, 2004a). Furthermore, exogenous mutp53 was found to enhance the growth rate of such cells (Deb et al, 2002;Scian et al, 2004b). Particular attention was devoted to the ability of mutp53 to impinge upon apoptotic pathways, primarily as this might be important in the context of efficient killing of tumor cells by chemotherapy and radiotherapy.…”
Section: Oncogenic Activities Of Mutp53mentioning
confidence: 99%
“…This transcription factor plays an important role in conferring an antiapoptotic state under a wide variety of conditions, including in many types of human cancers. Expression microarray analysis identified the NFKB2 gene as a target for positive transcriptional regulation by mutp53 (Scian et al, 2004b). This gene encodes the p100/p52 subunit of NF-kB.…”
Section: Mechanisms Of P53 Gofmentioning
confidence: 99%